MAKNA PERILAKU KOMUNIKASI ANTARA PECANDU NARKOBA DI KOTA PEKANBARU - Musthafalmi, Muhammad; Sari, Genny Gustina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The purpose of this study is to analyze the Behavior of Communication between Drug Addicts in Pekanbaru City. In addition, researchers also want to know the meaning of verbal and non verbal communication behavior between drug addicts in Pekanbaru City. This research uses qualitative method method with phenomenology approach as research design. The subjects in this study can not be determined the amount due to this research using data collection techniques Snowball. this study shows that drug addicts in Pekanbaru City in interacting using verbal and nonverbal communication behavior. As for the verbal communication used not as usual, they use verbal communication in the form of a term for the mention of the types of drugs they want to use. The term language used is divided into two types namely general terms and special terms, common terms that drug addicts use is Ck, while special terms such as dompeng, inex, lambuik, narek, niup, mompa, uuk, geleg. The novel communication used is to use body movements such as fisted hands and fingers.